Performance Evaluation Of Bandwidth Scheduling Techniques In Passive Optical Networks (International Journal of Engineering and Computer Science, 2015)
Abstract— Passive Optical Networks are thought to be the  next  step  in  the  development of  Access  Networks and  providing  broadband  access  in  the  ”last  mile” area.  Ethernet PONs (EPON) gain  the  most attention from  the  industry  as  they  offer  highly  flexible,  cost effective solution. In this paper we propose algorithms that provide Dynamic Bandwidth Allocation and shift the burden of queue management from the customer to the network, this results in less complicated and more generic equipment used on the customer’s premises. We show the results of simulations to validate the effectiveness of algorithms presented.